Dominance-based Matrix algorithm for Knowledge Reductions in Incomplete Fuzzy Information System - Lixin Fan; Qiang Wu (Institute of Advanced Engineering and Science, 2013)
In this paper，definitions of knowledge granulation and rough entropy are proposed based on dominance relations in incomplete fuzzy information system, and important properties are obtained. It can be found that using the definitions can measure uncertainty of an attribute set in the incomplete fuzzy information systems. A matrix algorithm for attributes reduction is acquired in the systems. An example illustrates the validity of this algorithm, and results of compared with other existing methods show that the algorithm is an efficient tool for data mining. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3725